The Application Of Health Protocols For SMP Negeri 5 Bilah Barat After Covid-19 - Melly Nova Diana; Pristiyono Pristiyono; Yudi Prayoga (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Corona Virus or what is often called Covid-19 is a virus that in early 2020 became a disease that attacked the community and was very scary for children and all citizens in the world. There are so many factors that cause the continued increase in Covid-19 patients, one of which is the public's ignorance about Covid-19, which makes it easy for the government to identify cases. Seeing from the potential of people who have to heed the government's appeal that we are required to work and worship at home for a while to prevent the transmission of Covid-19. The coronavirus outbreak was not only felt in the health sector but also penetrated all sectors including the education sector. In the education sector, the Covid-19 pandemic has created a policy to organize online education. Then Covid-19 also has an impact on the world of education starting from the basic education level to tertiary education. In the implementation of community service, the method used is socialization by explaining material about the Definition of Covid-19, Causes of Covid-19, Prevention of Covid-19 transmission, and How the coronavirus attacks our bodies. by using tools in the form of power points, distributing questionnaires, and practicing directly how to wash hands properly and correctly to students of SMP Negeri 5 Bilah Barat.